The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/pr11113098
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Frequency-Response Control Method for Electrode Boilers Supporting New Energy Accommodation

Tao Shi,
Zhiqiang Chen,
Shufeng Guo
et al.

Abstract: With the large-scale integration of new energy generation, represented by wind and photovoltaic power, into the power grid, the intermittency, randomness, and fluctuations of their output pose significant challenges to the safe and stable operation of the power system. Therefore, this paper proposes a control method for electrode boiler systems participating in rapid grid frequency response based on a fuzzy control strategy. This method improves the traditional electrode boiler control strategy, giving it char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Manni M et al [3] conducted a theoretical evaluation of the performance index of electrothermal coupling of an electrode boiler, and the results showed that the structure of the electrode boiler was the most effective, with an efficiency of 97%. Tao et al [4] proposed a control method based on a fuzzy control strategy for electrode boiler systems to participate in fast grid frequency response. This method improves the traditional electrode boiler control strategy and enhances the grid frequency regulation ability and system stability.…”
Section: Introductionmentioning
confidence: 99%
“…Manni M et al [3] conducted a theoretical evaluation of the performance index of electrothermal coupling of an electrode boiler, and the results showed that the structure of the electrode boiler was the most effective, with an efficiency of 97%. Tao et al [4] proposed a control method based on a fuzzy control strategy for electrode boiler systems to participate in fast grid frequency response. This method improves the traditional electrode boiler control strategy and enhances the grid frequency regulation ability and system stability.…”
Section: Introductionmentioning
confidence: 99%